Teaching Strategies for Students with Disabilities in Special Education Contexts: A Case Study at SLB Negeri Wonomulyo - Herianto; Abdullah; Geminastiti Sakkir (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study examines vocabulary teaching strategies used by an English teacher in a special education setting for students with hearing impairments in Indonesia, specifically at SLB Negeri Wonomulyo. Vocabulary is a fundamental component of language learning; however, students with hearing impairments encounter particular challenges due to limited auditory access, restricted language exposure, and diverse learning characteristics. These conditions often affect students’ ability to understand, retain, and use new vocabulary effectively. Therefore, implementing inclusive and adaptive instructional strategies is essential to support effective vocabulary acquisition and meaningful language learning. A qualitative descriptive research design was employed to obtain an in-depth understanding of instructional practices in the classroom. Data were collected through classroom observations, in-depth interviews with the English teacher and teaching assistant, and documentation of teaching materials used during the learning process. The collected data were analyzed thematically to identify recurring instructional patterns, teaching procedures, and vocabulary teaching strategies applied in the classroom context. The findings reveal that vocabulary instruction is conducted through several integrated strategies. These include individualized instruction tailored to students’ ability levels, multisensory learning through visual media, printed pictures, gestures, and Total Physical Response (TPR), collaboration with a teaching assistant to support classroom instruction and student engagement, and step-by-step instruction reinforced through frequent repetition. In addition, the teacher prioritizes the selection of functional vocabulary closely related to students’ daily lives in order to enhance meaningful learning, improve comprehension, and encourage practical language use in real-life situations. The study highlights that effective vocabulary instruction for students with hearing impairments relies on flexible, student-centered, and collaborative teaching practices. The findings provide empirical evidence supporting inclusive English language teaching in special education contexts and offer practical implications for teachers, practitioners, and future researchers working with learners with hearing impairments.